The degree of knowledge management practices in secondary schools applied to the curriculum system in Riyadh from the point of view of principals and teachers - Sheikh, Adel bin Habib (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify the degree of knowledge management practices in secondary schools applied to the curriculum in Riyadh city and the obstacles to their application from the point of view of school principals and teachers. The researcher followed the descriptive approach and applied the study tool to all the study society. (67) managers and (2279) teachers. The sample consisted of (67) managers and (342) teachers. The study resulted in several results. The most important of these were the following: 1. The knowledge management process was ranked at a general average (3.51). The process of application of knowledge reached an average of 3.67, followed by knowledge sharing with an average of 3.56, 3.48) followed by knowledge retention at an average of 3.45 and finally knowledge generation at an average of 3.37, all of which are "high". The obstacles to the implementation of knowledge management processes in secondary schools applied to the syllabus in Riyadh were at an average of (3.55). The suggestions that contribute to enhancing knowledge management operations in the target schools were (3.93) high and there were significant differences (0.01 = α) between the average responses of the sample groups on each of the degree of practice, constraints and suggestions according to the variable of the job, in favor of managers. The results showed that there were no statistically significant differences (0.01 = α) between the average responses of the sample groups on the degree of practice, constraints and suggestions according to the variable of functional experience. Differences were found depending on the variable training courses for those with more than two courses. In the light of the results, the study presented a number of recommendations and proposals aimed at activating the practice of knowledge management in the secondary schools applied to the curriculum system in Riyadh city.